Inovasi Teknologi Kreatif dan Edupreneurship dalam Kewirausahaan Digital Mahasiswa: Studi Kasus Aetheria Creative Agency di Era Industri 5.0 - Darmawan, Muhammad Yoggi Aqsal; Mizlan, Mizlan; Akbar, Muhammad Faizal; Malik, Muhammad Hisyam; Aula, Iqbal Ahsanul (PAKAR Pendidikan, 2025)
The development of the Industry 5.0 era requires college graduates to have adaptive digital entrepreneurship competencies in line with technological advances and social needs. The urgency of this research arises because colleges are faced with the challenge of preparing human resources who are ready to face the Industry 5.0 era while contributing to economic progress. However, many universities have not fully implemented digital entrepreneurship in their curricula, with education remaining theoretical without practical experience. This study examines the application of creative technological innovation and edupreneurship in student digital entrepreneurship through a case study of Aetheria Creative Agency in Yogyakarta. The approach used is qualitative with a case study method. Data was collected through indepth interviews with the CEO of Aetheria and direct observation at the location. Documentation of Aetheria's activities also served as a data source. The research findings show that Aetheria combines three main strategies: design, digitalization, and personalization, supported by technologies such as artificial intelligence (AI) and digital marketing. Students act as innovators, collaborators, and decision-makers within a human-centered digital entrepreneurship ecosystem. Digital innovation and edupreneurship impact the development of competencies such as critical thinking, cross-disciplinary collaboration, and digital literacy. This study underscores the importance of educational institutions in creating an integrated, solution-oriented, and relevant digital entrepreneurship ecosystem in the era of Industry 5.0.